The influence of Al-Dihlawi’s thoughts about Taklifin Hujjat Allah Al-Balighahon Mohd. Affandi Hassan’s thoughts on Islamic literature in Persuratan Baru - Narmi, Akalily; Abdul Rani, Mohd. Zariat; Kamarudin, Kamariah; Hajimaming @ Toklubok, Pabiyah (University of Malaya, 2023)
This study stems from the contribution of al-Imam al-Shaykh Ahmad Qutb al-Din Shah Waliyullah ‘Abd al-Rahim al-Dihlawi or better known by the name of Shah Waliyullah al-Dihlawi (henceforth al-Dihlawi), an Islamic scholar who was born in the 18th century in India. Among his most well-known book is Hujjat Allah al-Balighah which was published in 1732 and has been translated into several languages ​​including English, Indonesian and Malaysian language. This translation explains the importance of this book, especially the influence of al-Dihlawi’s ideas among Muslims outside the region of India. In this context, this study argues that al-Dihlawi’s ideas particularly on the philosophy of taklif in Hujjat Allah al-Balighah has also influenced the thoughts on Islamic literature in Malaysia. These influences are manifested in the postulation of “Persuratan Baru” (translated by Mohd. Affandi as “Genuine Literature”) by Mohd. Affandi Hassan. This study aims to discuss al-Dihlawi’s ideas on the philosophy of taklif in Hujjat Allah al-Balighah, and further conclude on his contributions to Mohd. Affandi Hassan’s Persuratan Baru. This study utilises the content analysis method for analysing study materials which are texts. This study finds that al-Dihlawi’s Hujjat Allah al-Balighah among other explicates the philosophy of taklif which refers to the imposition of divine accountability and responsibility upon man. By utilizing taklif, Persuratan Baru frames literary activity in the context of fitrah, i.e., the natural human inclination to submit to Allah S.W.T. The use of taklif in Persuratan Baru also enables the evaluation of literary works based on their portrayal of true Islamic values.